The mbo operon is specific and essential for biosynthesis of mangotoxin in Pseudomonas syringae. - Carrión Bravo, Víctor José; Arrebola-Díez, Eva María; Cazorla-López, Francisco Manuel; Murillo, Jesús; De-Vicente-Moreno, Antonio (PLOS, 2012)
Mangotoxin is an antimetabolite toxin produced by certain Pseudomonas syringae pv. syringae strains. This toxin is an oligopeptide that inhibits ornithine N-acetyl transferase, a key enzyme in the biosynthesis of ornithine and arginine. Previous studies have reported the involvement of the putative nonribosomal peptide synthetase MgoA in virulence and mangotoxin production. In this study, we analyse a new chromosomal region of P. syringae pv. syringae UMAF0158, which contains six coding sequences arranged as an operon (mbo operon). The mbo operon was detected in only mangotoxinproducing strains, and it was shown to be essential for the biosynthesis of this toxin. Mutants in each of the six ORFs of the mbo operon were partially or completely impaired in the production of the toxin. In addition, Pseudomonas spp. mangotoxin non-producer strains transformed with the mbo operon gained the ability to produce mangotoxin, indicating that this operon contains all the genetic information necessary for mangotoxin biosynthesis. The generation of a single transcript for the mbo operon was confirmed and supported by the allocation of a unique promoter and Rho-independent terminator. The phylogenetic analysis of the P. syringae strains harbouring the mbo operon revealed that these strains clustered together.
Keywords: Pseudomonas syringae; Bacterias fitopatógenas; Antimetabolitos; Fitotoxinas; Rizobacterias; Bacteria; Pseudomonas syringae; Mangotoxina; Biosíntesis; Factor de virulencia